Computerized or face-to-face oral testing? A tutor’s critical reflection of Japanese beginners’ test experience and learner anxiety - Chen, Julian; Hasegawa, Hiroshi; Collopy, Teagan (2020)
Despite its pedagogical benefits such as time-efficiency, uniformity, prompt feedback and reporting, computerised oral testing (COT) in languages other than English is nevertheless underutilized in the context of Japanese teaching and learning at the Australian university level. After a pilot study on the effectiveness of the COT delivery, the Japanese tutor’s critical reflection was investigated further via a follow-up survey and semi-structured interview. This reflective article reports on the tutor’s perspective as a COT assessor, its impact on students’ oral test performance including learner anxiety and administrative benefits, compared to her past experiences in employing the traditional face-to-face (F2F) oral interview test. The article concludes with the best practices and lessons learned from this COT approach that can be applied to other foreign language oral assessments using COT at the tertiary level.